Catalytic O- to N-Alkyl Migratory Rearrangement: Transition Metal-Free Direct and Tandem Routes to N-Alkylated Pyridones and Benzothiazolones - Mishra, Abhishek Kumar; Morgon, Nelson Henrique; Sanyal, Suparna; Robinson de Souza, Aguinaldo [UNESP]; Biswas, Srijit (Wiley, 2018)
The present study reports the synthesis of N-alkylated pyridones and benzothiazolones via O- to N-alkyl group migration under transition metal-free TfOH-catalyzed reaction conditions for the first time, to the best of our knowledge. Primary as well as secondary alkyl groups smoothly migrate under the present reaction conditions. Moreover, a minor modification of the protocol used in this study is found to be applicable for an entirely new tandem synthesis of 2-alkoxy-N-heterocycles from the simplest starting materials in a solvent-free reaction conditions. Density Functional Theory (DFT) calculation identifies the energy species associated with the rearrangement, whereas, mechanistic experiments explore the role of the catalyst as the alkyl group transfer mediator.
Keywords: Benzothiazolones; DFT; Metal-free; Pyridones; Rearrangement; Tandem